KONSTRUKSI UNSUR PERSELISIHAN TERUS-MENERUS SEBAGAI ALASAN PERCERAIAN: STUDI KOMPARATIF PENGADILAN AGAMA DAN PENGADILAN NEGERI - Callysta Adzhani Syahirah; Heri Hartanto (Verstek, 2025)
This research aims to examine the comparative analysis of how District Courts and Religious Courts interpret the phrases "continuous disputes" and "irretrievable breakdown of marital harmony," as well as the reconstruction of these phrases as legitimate grounds for divorce in court. This study employs normative legal research with a statutory approach and a case study approach. The types of data utilized are primary and  secondary  data.  The  legal  materials  were  collected  through  library  research.  The  data  analysis technique  employed  in  this  research  is  inductive  analysis.  The  findings  of  this  research  indicate  that  in interpreting  the phrase "continuous disputes,"  both the  District Court and the Religious  Court utilize the same  legal  basis,  namely  the  Circular  Letter  Number  3  of  2023  concerning  the  Enforcement  of  the Formulation  of  the  Results  of  the  Plenary  Meeting  of  the  Chambers  of  the  Supreme  Court  of  2023  as Guidelines for the Implementation of Court Duties. Conversely, in interpreting "irretrievable breakdown of marital  harmony,"  the  consideration  in  both  the  District  Court  and  the  Religious  Court  revolves  around whether  or  not  there  have  been  attempts  by  family  members  to  reconcile  the  disputing  spouses.  The distinction lies in the fact  that  the Religious Court's provisions  are regulated in greater detail within the Qur'an and Hadith. It is suggested that these interpretations should also be explicitly stated in the articles or the explanatory notes of the relevant legal provisions.